WHY DOES THE REPORT OF SPECIAL ALLOCATION FUNDS IN LOCAL GOVERNMENT OVERDUE? - Arif, Alma; Rauf, Muhammad; Khaq, Akhsanul; Akbar, Bahrullah; Pramono, Agus Joko (Moestopo International Review on Social, Humanities, and Sciences, 2025)
This study aims to identify the factors that hinder the reporting process and describe the ideal aspects of reporting the Nonphysical Special Allocation Fund for Women and Children Protection Services in Dumai City. This research uses data from the report on the realization of absorption and realization of the use of Non-physical Special Allocation Funds for Women and Children Protection Services in Dumai City in 2020-2022 and primary data from interviews. The research method uses a constructivist paradigm with an inductive qualitative approach and data analysis using thematic analysis methods. The method of determining the validity of research data uses data source triangulation techniques. Factors caused the report of special allocation funds overdue are poor internal coordination, lack of understanding of the reporting system caused by lack of socialization and ineffective use of communication media, and unsynchronized reporting between agencies and technical implementation units caused by the complexity of the reporting format and the absence of the person in charge of reporting are inhibiting factors in the reporting process. A good coordination process and socialization related to the reporting system are ideal aspects that should be done so that the reporting process becomes better.